The Mediating Effects of Work-Life Balance on the Relationship of School Heads’ Leadership Practices and Teachers’ Work Satisfaction - Borreba, Lelet; Potane, Joel (Journal of Interdisciplinary Perspectives, 2024)
This study sought to determine whether work-life balance mediates the relationship between school leaders' leadership and teachers' job satisfaction. The descriptive-correlational research design was used in the study, which involved 176 randomly selected public school elementary teachers from the Division of Misamis Oriental, Philippines. The main data source for this study was a modified, and validated survey questionnaire. The study found that most respondents were female and that the 31-45 age bracket is particularly well represented. Furthermore, the prevalence of Teacher I positions suggested that the study sample was primarily composed of entry-level teaching roles. In terms of service years, those with 6-10 years were the largest group. However, in terms of civil status, the results revealed a predominance of married people. The most common category of children is those with 2-3 children, and the most common income category is 25,001-30,000 per month. In addition, work-life balance does not differ significantly by gender, age, service years, civil status, children, or income level. It implies that different groups may have unique needs and preferences for maintaining and achieving work-life balance. Furthermore, no direct correlation has been found between work-life balance and satisfaction; therefore, school administrators must investigate this relationship further. The indirect, direct, and total effects were not statistically significant, suggesting that work-life balance does not mediate the relationship between leadership and job satisfaction. Schools and educational institutions can investigate further the benefits of focusing on leadership development programs that improve leadership skills and practices to positively influence teacher satisfaction.